Sample preparation and data collection for serial block face scanning electron microscopy of mammalian cell monolayers - Antao, Noelle V.; Sall, Joseph; Petzold, Christopher; Ekiert, Damian C.; Bhabha, Gira; Liang, Feng-Xia (PloS one, 2024)
Volume electron microscopy encompasses a set of electron microscopy techniques that can be used to examine the ultrastructure of biological tissues and cells in three dimensions. Two block face techniques, focused ion beam scanning electron microscopy (FIB-SEM) and serial block face scanning electron microscopy (SBF-SEM) have often been used to study biological tissue samples. More recently, these techniques have been adapted to in vitro tissue culture samples. Here we describe step-by-step protocols for two sample embedding methods for in vitro tissue culture cells intended to be studied using SBF-SEM. The first focuses on cell pellet embedding and the second on en face embedding. En face embedding can be combined with light microscopy, and this CLEM workflow can be used to identify specific biological events by light microscopy, which can then be imaged using SBF-SEM. We systematically outline the steps necessary to fix, stain, embed and image adherent tissue culture cell monolayers by SBF-SEM. In addition to sample preparation, we discuss optimization of parameters for data collection. We highlight the challenges and key steps of sample preparation, and the consideration of imaging variables.